Mining in the Newspapers: Local and Regional Media Representations of Mineral Exploration and Mining in Finland, Germany, and Spain - Lyytimäki, Jari; Benighaus, Ludger; Gómez, Javier; Benighaus, Christina; Kauppi, Sari; Kotilainen, Juha M.; Mononen, Tuija; del Rio, Virginia (Mining, Metallurgy & Exploration, 2021)
Abstract The understanding of public debates over mineral exploration and mining largely originates from exceptional situations such as mining accidents of conflicts. Less is known about how mining is portrayed and understood under more conventional settings. What storylines dominate the local day-to-day public debate? This article presents results from a comparative case study focusing on newspaper coverage of mineral exploration and mining in three European countries representing different geological and socio-economic contexts. Newspaper articles from the Geyer-Erzgebirge region in Germany, the Andalusia region in Spain, and Northern Finland are studied. The sample looks into the period between September 2018 and February 2020 and shows that regional newspapers report about mining issues relatively intensively even in the absence of major accidents or other media events causing peaks of attention. The tone of the articles is generally neutral to positive towards mining activities, reflecting the specific local settings, historical experiences, and future expectations. Despite the different contexts of the three countries, there were considerable similarities to the topics highlighted, including common themes of mining revival, mining events and social interaction, history of mining, and damages related to mining. Past, present, and future employment opportunities related directly or indirectly to the mining sector are key storylines. Another recurrent underlying theme is the need to balance environment and safety risks and socio-economic prosperity, typically covered through ordinary disputes among the mining sector, public authorities, regional non-governmental organizations, and local initiatives.